Nose-Flap Devices Used for Two-Stage Weaning Produce Wounds in the Nostrils of Beef Calves: Case Report - Valente, Tiago S. [UNESP]; Ruiz, Lucas R. B. [UNESP]; Macitelli, Fernanda; da Costa, Mateus J. R. Paranhos (MDPI, 2022)
This case report aims to describe the occurrence of negative impacts of wearing nose-flap devices on beef calves subjected to the two-stage weaning method. Forty-one calves, twenty-one pure Nellore and twenty F1 Angus-Nellore, were weaned on average at 236 days of age. Commercial nose-flap devices were fitted in the nostrils of the calves (d0) to prevent suckling and removed five days later (d5). Individual body weights were assessed at d0 and d5, and average daily gain (ADG) was calculated. At d5, during nose-flap device removal, it was noted that 26.8% of the calves lost the nose-flap device; however, all of them had wounds in their nostrils (no injuries in the nostrils had been observed on d0). To assess the severity of these injuries, an impairment score was assigned to each calf, ranging from 1 = no lesions to 5 = injured with purulent discharge. A logistic regression model was fitted to evaluate the effect of sex and genetic group on nose-flap retention (kept or lost). The retention rate did not differ (p > 0.05) between sex and genetic groups. All calves showed at least open wounds of the nasal septum (score 2), including those that lost the nose-flaps before d5. Almost half of the calves showed weight loss during this period. We conclude that there is a considerable risk of the two-stage weaning method compromising the physical integrity of the nostrils of beef calves through the use of these devices, and due to this, it should not be referred to as a low-stress weaning practice for beef calves.
Keywords: animal welfare; anti-suckling device; cow-calf operation; nasal abrasions